Isolated intracranial Rosai Dorfman Disease without nodal involvement. - Aziz, Peer Asad; Raja, Riaz Ahmed; Khimani, Vashdev; Nasir, Zeeshan; Aziz, Pir Abdul Ahad; Qureshi, Noorulain; Pathan, Sanaullah; Aitzaz Ahmed (International Journal of Endorsing Health Science Research, 2019)
Background: Rosai Dorfman disease is a benign lymphohistiocytosis that often involves lymph nodes and present as massive painless lymphadenopathy with sinus histiocytosis. Usually systemic involvement and with rare intracranial and extremely rarely intracranial involvement without the involvement of lymphadenopathy. Case Presentation: We presented a case of 60 years old female with seizures and left side weakness and no lymphadenopathy. The MRI revealed contrasting right frontal homogenously enhancing convexity mass. Management & Results: The patient was kept on antiepileptic medications but soon presented with fits and slight expansion in frontal mass. Surgery was performed (right frontal craniotomy), the mass was surgically resected and biopsy indicated Rosai Dorfman disease. Conclusion: By now only 7 of such cases are reported and prognosis of the disease is not poor if surgically treated however other measures including radiotherapy, chemotherapy, steroids are not very effective for treating the disease. And due to the rarity of disease suspicion of such disease should always be kept as a key differential in homogenously enhancing lesions with dural involvement with or without lymphadenopathy.